Core Ethical Values of Character Education Based on Sundanese Culture Value - Hisny Fajrussalam; Aan Hasanah (IJECA (International Journal of Education and Curriculum Application), 2018)
This paper is motivated by the moral decadence that occurs in West Java as a Sundanese society. This paper intends to re-explore ethical values that should be the basis of Sundanese people's lives in West Java. This research uses qualitative. Data taken from the author's observational that are felt and experienced in everyday life. Research shows that education takes an important role in efforts to foster a moral attitude of society. Education in question is character education based on Sundanese cultural values. So hopefully the community can become an identity that always holds the wisdom of a good Sundanese culture. Some ethical values of Sundanese culture that can be found are welfare, health, care for the environment, moderate, hard work, discipline, politeness, honesty, upholding the truth, mutual cooperation, social solidarity, positive thinking, mature calculation, education, gender management, preservation and preservation Sundanese culture. The values of Sundanese culture can be classified into 2 (two), namely prosperity/welfare and peace/goodness that are all reflected in outlook on life, oral traditions, language, and pro-social behavior. These values are very relevant to the essential value of the Koran. Based on the values inherent in the Sundanese community, it should be able to create a climate that brings the community to Islamic values. Thus, we will go to the society that Islam aspires for, namely a society where every aspect of life breathes religious values.